Synthesis of Magnetic Nanoparticles under Ambient Temperature from Single Iron Salts and Characterization - Sikder, Belal Hossain; Rashid, Shah Samiur; Mohd Hasbi Bin Ab. Rahim; Aizi Nor Mazila Binti Ramli; Rashidi Bin Roslan (Science & Technology Asia, 2022)
Magnetic nanoparticles (MNPs) have gained a lot of attention from scientists since they offer a great potential in chemistry, biology, medicine, and physics. The synthesis of various types of MNPs for nano-medical products has received a special attentiveness in the recent era. Several methods have been developed for the synthesis of MNPs but most of them need more than one iron precursors, special apparatus, and temperature restriction. In this study, single iron salts and room temperature were considered for the MNPs synthesis which is eco-friendly as well as green methods to reduce the usage of the thermal (heat) energy more Iron salts. An anhydrous Fe (III) salt; ferric chlorides (FeCl3) were reduced by using potassium iodide (KI) solution. The molar ratio of two salts was 2:1 respectively. The iodine precipitate is filtered out, and the filtrate is hydrolyzed with an ammonium hydroxide solution. Magnetic nanoparticles were synthesized as black precipitated and decanted by external magnet and dried in a desiccator at room temperature. The MNPs were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscopy energy dispersive X-ray (FESEM-EDX), and vibrating sample magnetometer (VSM). The FTIR spectrum revealed the vibrational stretching band of Fe-O at the peak at 580 m cm−1. The crystalline nature of MNPs was determined by XRD analysis. The size of nanoparticles under TEM was 20±2.0 nm. The elemental composition of black magnetite was estimated 51.01 % iron, 38.70% oxygen by EDX. The saturation magnetization of the synthesized nano particles was 66.74 emu/g. This MNPs could be applied in drug delivery systems, protein, enzyme immobilization purposes.